Engaging older adults with a migration background to explore the usage of digital technologies in coping with dementia - van Leersum, Catharina M.; Konrad, Kornelia E.; Siebrand, Egbert; Malik, Zohrah B.; den Ouden, Marjolein E. M.; Bults, Marloes (Frontiers in Public Health, 2023)
Background: Coping with dementia can imply particular challenges for people with a migration background due to diversity in life course, personal characteristics, and their living environment. Some of the services available for people with dementia include digital technologies for care, to provide health services and maintain or increase participation, independence, and safety. This study aims to explore the role of digital technology for coping with dementia in the lives of older adults with a migration background, and possibilities to engage and collaborate with older adults. Methods: The study combined a qualitative interview-based approach with citizen science principles in the design and execution of a project studying the use of Anne4Care. Results and discussion: Participants valued that technology should provide health benefits and fit into aspects of their daily lives. Anne4Care was considered helpful in staying independent and connecting to loved ones in their country of birth. The participants needed to learn new competences to work with the device, and not all had the material prerequisites, such as an internet connection. Still, this learning process was considered purposeful in their life, and the virtual assistant could be integrated in care and daily practices. The involvement of the older adults with dementia as co-researchers made them feel valuable and being an equal partner during this research. An important prerequisite for the involvement of older adults with a migration background were existing relations with carers and care organisations. Conclusion: Digital care technologies to cope with dementia can become a valuable part of care practices and lives of older adults with a migration background. Involving older adults in the development of technology, acknowledges their expertise and needs, and working together in short iterations to adapt the technology to their specific needs and situations was experienced valuable by the researchers, older adults, and care professionals.